Ishihara test in 3- to 6-year-old children - Choi, Sang Yul; Hwang, Jeong-Min (Japanese journal of ophthalmology, 2009)
Purpose To investigate the efficacy of a modified Ishihara color test in preschoolers. Methods The Ishihara test was performed to screen 115 children 3 to 6 years of age for color vision deficiency. Children who could not read numbers were instructed to trace the shapes of the numbers and of colored winding lines on the test plates using a cotton-tipped applicator. The ability of the children to understand and complete the test was investigated. Results The Ishihara test was satisfactorily taken by 96.5% of the 115 children. Two 3-year-olds and two 4-year-olds did not understand the test. Thirty-five percent of the 3-year-olds could not read numbers but successfully used the tracing method. Three of the 51 boys and none of the 64 girls were considered color deficient. Conclusion The modified Ishihara test was successfully performed by children aged 3 to 6.